Características morfogênicas e estruturais de cultivares de azevém - Oliveira, Eduarda Proença de (2023)
Species Lolium multiflorum Lam., also known as ryegrass, is a forage grass that perfectly expresses its productive potential in the agricultural system of southern Brazil. Among the ryegrass cultivars, there are cultivars with different genetic loads, such as diploid (2n) and tetraploid (4n). However, many variables of these genotypes are still little known, creating the need for studies regarding their morphogenic and structural characteristics. In this sense, understanding the behavior of the forage ecosystem in the face of variations in natural resources becomes a tool capable of assisting in the development of sustainable management goals. This study was carried out with the objective of evaluating the morphogenesis of different cultivars of ryegrass intercropped with red clover (Trifolium pratense L.) and gherkin (Lotus corniculatus L.). The morphogenesis evaluations were carried out by identifying the ryegrass tillers with colored plastic rings, at four points representing the pasture canopy height. On these occasions, the heights of the canopy, pseudostem, extended tiller and the length of the expanded, expanding and senescent leaves were measured. The experimental design was randomized blocks, with repeated measures in time, with three treatments and three area replications. The experimental treatments were the ryegrass cultivars, Bill Max, Bolt and Selva, during the pasture evaluation periods. There was no interaction between cultivars x evaluation periods for the variables canopy height, forage supply, leaf blade supply, forage mass, leaf blade mass, number of green leaf blades, stocking rate, phyllochron, leaf life span, leaf expansion rate and leaf senescence rate, except for the leaf appearance rate variable. Structural characteristics did not differ between cultivars, but did differ between evaluation periods. The phyllochron differed between cultivars and between evaluation periods. Higher mean phyllochron values were observed for the Bolt and Selva cultivars when compared to the Bill Max cultivar. For leaf life span there was no difference between cultivars and there was difference between evaluation periods. The leaf expansion rate differed between cultivars and between evaluation periods. The leaf senescence rate differed between cultivars and between evaluation periods. The leaf appearance rate was higher in all cultivars, in all evaluation periods, except in the second evaluation period, in which the Selva cultivar showed a lower leaf appearance rate. The leaf appearance rate was higher in the first three evaluation periods, regardless of the cultivar. The evaluated cultivars show differences in terms of morphogenetic characteristics, suggesting the adoption of specific management strategies for each ryegrass cultivar. The tetraploid genotype Bill Max of ryegrass has a lower phyllochron, that is, it needs less thermal accumulation for the emergence of new leaves in the tiller, thus being considered a cultivar with high leaf turnover that ensures good regrowth after defoliation.